Evaluation of the sailent features in Indian currency notes - Sharma, Sanya; Rohatgi, Shipra; Mansour, Saleh (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
Security features are topographies invisible to the naked eye, such as micro-printing or features visible in ultraviolet, transmitted, and oblique light. The present paper focuses on the examination of Indian currency notes such as 2000, 500, 200, 100, 50, 20, and 10 in different light sources and with the help of a compound microscope. This kind of examination is very useful when it comes to distinguishing counterfeit currency from genuine one. Crime is increasing day by day, and so is the making of false currency – this study discusses the numerous security or hidden features which are invisible to the naked eye, and therefore may very well be missed by the potential perpetrator. It is the responsibility of the government along with the issuing authority to incorporate these structures into all travel and security documents, including passports, voter-id cards, and many others. These features are implemented either during the manufacturing of the paper itself (e.g., fluorescent fibres) or at the time of printing (e.g., microprinting, watermarks, and other fluorescent features).
Keywords: currency notes; micro-printing; fluorescence; transmitted light; counterfeit currency